Intrapreneurship to engage employees: role of psychological capital. Issue 6 (9th July 2020) - Pandey, Jatin; Gupta, Manish; Hassan, Yusuf
Abstract : Purpose: Intrapreneurship is gaining traction in organizations to buckle up for the dynamic business environment. Scholars have argued that intrapreneurship increases positivity at work and helps employees attach themselves better with their job. However, empirical evidence suggests that these relationships do not exist. The objective of this paper is to examine the mediating role of psychological capital (PsyCap) in the relationship between intrapreneurship and work engagement. Design/methodology/approach: Data were collected through an online survey. Responses from 309 employees working in different industries in India were analysed. Structural equation modelling (SEM) was used to analyse the hypothesized relationships. Findings: The results show that there exist positive relationships among intrapreneurship, psychological capital (PsyCap) and work engagement. Further, it was observed that the PsyCap partially mediates the relationship between intrapreneurship and work engagement. Practical implications: Managers may not only encourage intrapreneurial behaviour in their organizations but also ensure that the employees are psychologically capable (high on PsyCap). It would enable the employees to engage themselves wholeheartedly into their work. Originality/value: To the best of the authors' knowledge, this study is one of its kinds to relate intrapreneurship with PsyCap and work engagement.